2006
DOI: 10.1111/j.1600-0609.2006.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant immature CD8α+ dendritic cells prevent graft‐vs.‐host disease but do not increase the risk of leukemia recurrence

Abstract: Graft-vs.-host disease (GVHD) remains the major limitation of allogeneic bone marrow transplantation (BMT) and stem cell transplantation, and leukemia recurrence is another important complication in leukemia treatment. Immature CD8alpha+ dendritic cells (DC) have good potential in GVHD treatment and immunological tolerance studies. To find a new way to prevent GVHD, not increasing the risk of leukemia recurrence, in this study, predominant CD8alpha+ immature DC were induced from murine bone marrow (BM) cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In a murine model of GVHD, a single treatment with age-matched, syngeneic DCreg attenuated allogeneic-BMT induced GVHD, while maintaining the GVT response [89,91,241,265]. Importantly, our studies also demonstrated amelioration of GVHD in older mice following allogeneic BMT (Chapter II).…”
Section: Cells (As Well As DC and B Cells) Would Be Included In The Lsupporting
confidence: 52%
See 1 more Smart Citation
“…In a murine model of GVHD, a single treatment with age-matched, syngeneic DCreg attenuated allogeneic-BMT induced GVHD, while maintaining the GVT response [89,91,241,265]. Importantly, our studies also demonstrated amelioration of GVHD in older mice following allogeneic BMT (Chapter II).…”
Section: Cells (As Well As DC and B Cells) Would Be Included In The Lsupporting
confidence: 52%
“…In a murine model of GVHD, a single treatment with age-matched, syngeneic DCreg attenuated complete MHC mismatched allogeneic-BMT induced GVHD, while maintaining the GVT response [89,91,241,265].…”
Section: Future Directionsmentioning
confidence: 99%
“…Some DC subsets are also proved to induce immunotolerance [4,[21][22][23] . It has been reported that CD8α + DCs could induce tolerance [9,16,22] , but there has not been reported whether tumor antigen-pulsed CD8α + DCs can induce GVT/GVL. EL9611 is a leukemia cell line established in China [12] , and there has not been any report on its antigenicity and its application in GVL research by now.…”
Section: Discussionmentioning
confidence: 99%
“…However, after CD8α + DCs were pulsed by tumor antigen, T cell proliferation was significantly enhanced with the CD8α + DC/T ratio. Our previous studies found that non-antigen-pulsed immature CD8α + DCs expressed low level of MHC and Ⅱ costimulatory molecules on the surface, could not stimulated T cell proliferation effectively, and could prevent GVHD [6,7,9,11] . In this study, we found that tumor antigen-pulsed immature CD8α + DCs could present antigens and stimulate T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation